Anatomical Characteristics and Fiber Morphology of Palmyra Wood (Borassus Flabellifer L.) Originating from Timor Island, East Nusa Tenggara Province - Rynaldo Davinsy; Adrin Adrin; Lora Septrianda Putri; Melkianus Pobas; Luisa Moi Manek; Ni Kade Ayu Dewi Aryani; Mahardika Putra Purba; Emi Renoat; Yudhistira Ardhyana Nugraha Rua Ora; Ika Kristinawanti; Kristianto Wibison So; Yakub Benu (Biology, Medicine, & Natural Product Chemistry, 2026)
Palmyra wood (Borassus flabellifer L) is a widely distributed palm species in tropical Asia, including East Nusa Tenggara (NTT). Its wood has potential applications in construction, handicrafts, and bioenergy, making anatomical and fiber morphology studies essential for understanding its value and utilization. This research used palmyra wood samples from Timor Island, Kupang, in the form of discs with a diameter of approximately 30 cm, taken from the base, middle, and upper parts of the stem. Test specimens were prepared in 2 × 2 × 5 cm dimensions, and analyses were conducted following standard procedures. The results revealed that palmyra wood possesses anatomical characteristics typical of palms, namely collateral closed-type vascular bundles irregularly scattered within parenchymatous ground tissue, with phloem located outside the xylem. Fiber morphology exhibited a gradual reduction in dimensions from the base to the tip of the stem, with fiber diameters ranging from 38.48 to 15.64 µm, wall thickness from 17.09 to 6.92 µm, and lumen diameters from 13.02 to 5.42 µm. The number of vascular bundles also decreased from 3.0 at the base to 1.21 at the tip, with bundle density ranging from 0.49 to 0.20/mm². Overall, palmyra wood exhibits stronger mechanical properties at the base of the trunk, as demonstrated by the anatomy and morphology of its fibers, thus increasing its biological durability. These findings highlight its potential as a structural material, craft resource, and bioenergy feedstock in dryland regions such as NTT.